Ukraine and Europe : cultural encounters and negotiations - Brogi Bercoff, Giovanna; Pavlyshyn, Marko (University of Toronto Press, 2017)
"Ukraine and Europe challenges the popular perception of Ukraine as a country torn between Europe and the east. Twenty-two scholars from Europe, North America, and Australia explore the complexities of Ukraine's relationship with Europe and its role the continent's historical and cultural development. Encompassing literary studies, history, linguistics, and art history, the essays in this volume illuminate the interethnic, interlingual, intercultural, and international relationships that Ukraine has participated in. The volume is divided chronologically into three parts: the early modern era, the 19th and 20th century, and the Soviet/post-Soviet period. Ukraine in Europe offers new and innovative interpretations of historical and cultural moments while establishing a historical perspective for the pro-European sentiments that have arisen in Ukraine following the Euromaidan protests. Giovanna Brogi Bercoff is the President of the Italian Association of Ukrainian Studies. Marko Pavlyshyn is a professor of Ukrainian Studies in the School of Languages, Literatures, Cultures, and Linguistics at Monash University. Serhii Plokhy is the Mykhailo Hrushevsky Professor of Ukrainian History at Harvard University."--